To Investigate the Effect of Magnetic Resonance Imaging (MRI) and Diffusion Tensor Imaging (DTI) in the Diagnosis of Mild Craniocerebral Injury. - Lei, Xiaoyan; Qin, Dan; Zhu, Gangming (BioMed Research International, 2022)
In order to assess the value of magnetic resonance imaging (MRI) and diffusion tensor imaging (DTI) in microscopic brain scans. Diffusion tensor imaging (DTI) and magnetic resonance spectroscopy (MRI) changes over time in patients with traumatic brain injury (TBI) show a relationship between recovery from coma and overall Glasgow prognostic parameters. The value of DTI combined with MRI in evaluating TBI has been investigated. 10 patients with TBI received 10 evaluations of magnetic resonance imaging, DTI and MRI scans. Thalamic plate nucleus, reticular nucleus, and retinal developmental activity were measured in normal controls and TBI coma (2-3 weeks) and mild (>4 weeks) patients. Anisotropy, mean diffusion coefficient, axial diffusion coefficient, and radial diffusion coefficient were measured using MRI together with acetylaspartic acid, choline, creatinine, and lactic acid. Independent control t-tests were conducted between controls and TBI patients, and 1-test paired between moderate and severe injuries, and regression and correlation were evaluated. Evaluated for all measures and treatments. DTI and MRI scores in TBI patients differed from normal controls. DTI and MRI can predict the prognosis of TBI patients better. The limitations of the thalamus-retinal activation system are gradually restored. axial diffusion coefficient and radial diffusion coefficient can be used to evaluate the reliability of comatose patients with TBI. DTI and MRI scans of the patient's brain can predict recovery and guide treatment in TBI coma patients.